Effect of Phosphorus and Zinc with and without Vermicompost on Yield and Nutrient uptake of Fennel Crop (Foeniculum vulgare Mill.) - Abha, Abha; Sharma, Yogesh (Annals of Arid Zone, 2016)
two year experiment was conducted to find out the effect of vermicompost, phosphorus and zinc on yield and nutrient uptake of fennel. Application of 2 t vermicompost ha-1 significantly increased the seed, stover yields and phosphorus and zinc uptake of seed and stover. Application of 40 kg P2O5 ha-1 had 43.16 and 25.89% higher seed and stover yield, respectively over control. Phosphorus uptake in seed and stover and zinc uptake in seed and stover increased significantly up to 40 kg P2O5 ha-1. Application of 6.0 kg Zn ha-1 significantly increased seed and stover yield and phosphorus uptake in seed. Zinc uptake by seed and stover increased significantly up to 9.0 kg Zn ha-1. Combined application of 2 t vermicompost ha-1 and 40 kg P2O5 ha-1 resulted in the highest seed (1377 kg ha-1) yield and was found significant for phosphorus and zinc uptake by seed. The interaction effect of treatment combination 2 t vermicompost + 6 kg Zn ha-1 was found significant for phosphorus uptake by seed. However, in zinc uptake by seed the treatment combination 2 t vermicompost + 9 kg Zn ha-1 was found significant. The treatment combination of P40Zn6 (40 kg P2O5 ha-1 + 6.0 kg Zn ha-1) was found significant for seed and stover yield and phosphorus uptake by seed.